Quebec’s English-speaking community and the partnership approach of its networks in health - Pocock, Joanne (Linguistic Minorities and Society, 2021)
This article discusses the networking and partnership approach of improving access to public health and social services, with an interest in informing best practices for official language populations in a minority context. The case of Canada’s official language minority residing in the province of Quebec and its Community Health and Social Services Network (CHSSN) is explored. Elements that support or inhibit partnership functioning, including innovative community-based participatory evaluation (CBPE) techniques, are explored. The contribution of the approach in improving the situation of Quebec’s minority language communities with respect to their health care access is highlighted. Keywords: official language minority communities, intersectoral partnerships, access to public health care, language policy, community-based participatory evaluation (CBPE)

English-language health and social services access in Québec. Baseline data report 2015-2016 - Pocock, Joanne (Community Health and Social Services Network, 2016)

Accès aux services de santé et aux services sociaux en anglais au Québec. Rapport de données de base 2005-2006 - Pocock, Joanne (Réseau communautaire de santé et de services sociaux, 2006)

Rapport sur les priorités des communautés d’expression anglaise du Québec en matière de santé et de services sociaux - Carter, Jim; Pocock, Joanne (2022)
pages: 34

Accès aux soins de santé pour les communautés québécoises d’expression anglaise – Principaux enjeux et besoins en matière de recherche - Shoumarova, Lina; Pocock, Joanne; Donovan, Patrick; O'Donnell, Lorraine (Université Concordia, 2025)
Le présent document résume les travaux de recherche qui ont été menés récemment sur l’accès aux services de santé et aux services sociaux pour la communauté de langue officielle en situation minoritaire (CLOSM) anglophone du Québec. S’appuyant sur la Bibliographie sur le Québec anglophone, la Bibliothèque ouverte du savoir communautaire et le centre de documentation du Réseau communautaire de santé et de services sociaux (CHSSN), il met en lumière les principaux thèmes traités, les lacunes dans la recherche et les domaines où d’autres travaux de recherche doivent être menés en priorité.